2018
DOI: 10.17628/ecb.2018.7.1-9
|View full text |Cite
|
Sign up to set email alerts
|

Dimeric Molecular Aggregation Motif in Crystal of 2,7-Diethoxy-1-(4-Nitrobenzoyl)naphthalene: Correlation of Single Molecular Structure, Molecular Accumulation Structure and Non-Covalent-Bonding Interactions

Abstract: Crystal structure of 2,7-diethoxy-1-(4-nitrobenzoyl)naphthalene C21H19NO5, is reported and discussed on the characteristics of the spatial organization of single molecule and molecular aggregation as contrasted with a homologous compound. The molecular structures of these compounds differ only in the kind of alkoxy group of 2,7-positions of the naphthalene rings, i.e., ethoxy groups for title compound and methoxy groups for homologue. In single molecular crystal structures of these compounds, 4-nitrobenzoyl gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Conformational studies of hydroxyaryl ketones in the solid state and in solution have attracted considerable interest (Siskos et al, 2015;Nonhebel, 1968). Since the discovery of an effective method for diaroylation at the 1,8(peri)-positions of the naphthalene ring core and the related reactions (Okamoto & Yonezawa, 2009;Okamoto et al, 2011;Okamoto, Mitsui et al, 2012), we have reported on the spatial organization of 1,8-diaroylated naphthalenes and homologous compounds in both the solid state and solution Yoshiwaka et al, 2015;Okamoto et al, 2015;Ohisa et al, 2018). In the crystal structures of these compounds, which have non-coplanar accumulated aromatic rings, molecules are arranged by weak ISSN 2056-9890 intermolecular interactions, such as non-classical hydrogen bonds and van der Waals interactions.…”
Section: Chemical Contextmentioning
confidence: 99%
“…Conformational studies of hydroxyaryl ketones in the solid state and in solution have attracted considerable interest (Siskos et al, 2015;Nonhebel, 1968). Since the discovery of an effective method for diaroylation at the 1,8(peri)-positions of the naphthalene ring core and the related reactions (Okamoto & Yonezawa, 2009;Okamoto et al, 2011;Okamoto, Mitsui et al, 2012), we have reported on the spatial organization of 1,8-diaroylated naphthalenes and homologous compounds in both the solid state and solution Yoshiwaka et al, 2015;Okamoto et al, 2015;Ohisa et al, 2018). In the crystal structures of these compounds, which have non-coplanar accumulated aromatic rings, molecules are arranged by weak ISSN 2056-9890 intermolecular interactions, such as non-classical hydrogen bonds and van der Waals interactions.…”
Section: Chemical Contextmentioning
confidence: 99%